Studi Implementasi KKP Top Schedule dalam Audit di Kantor Akuntan Publik (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study reviews the implementation of Top Schedule in the audit process at KAP Dony Firliawan. The occurrence of an effective and efficient Top Schedule in the audit, whether it maintains data quality even though its appearance is simple, and how easy it is for Top Schedule to adapt to different clients. Through interviews, observations, and document checks, the author found that Top Schedule is very helpful for auditors because it makes the workflow clear and efficient. Although simple, it still guarantees data accuracy because each number can be rechecked to the original source. Interestingly, Top Schedule is also very flexible, it can be adjusted for various types of clients. In conclusion, Top Schedule at KAP Dony Firliawan proves that a simple presentation can produce a fast, quality, and adaptive audit.